Factors Influencing PhilHealth Coverage and In-patient Benefit Utilization of Filipino Children under Five - Maria Elizabeth Angeline D. Puyat (Philippine Institute for Development Studies (PIDS), 2013)
According to the 2008 National Demographic and Health Survey (NDHS) report, children under 5 are more likely to use in-patient care than other age groups. These children are not only more vulnerable to getting sick, but are also at risk of incurring high health expenditures if they are without health insurance. Using the 2008 NDHS dataset, this study focused on the coverage and in-patient benefit utilization of children under 5, who are dependents of the Philippine Health Insurance Corporation (PhilHealth). Unique to this analysis was the shift in focus of coverage and utilization from the traditional angle of primary members to the dependents.Descriptive analyses revealed that PhilHealth covered only 33.93 percent of the under-5 population, and of those PhilHealth dependents who were confined in a hospital, 67.59 percent used PhilHealth as a source of payment. Logistic regression analysis determined that age and educational attainment of the household head, region, and wealth index were significant factors that influenced coverage. Moreover, it was found that confinement in a private facility and for longer periods of time increased the probability of in-patient benefit utilization for PhilHealth dependents. These results will be useful for PhilHealth as they create evidence-based initiatives to attain Universal Health Coverage.
Keywords: 330; health insurance; Philippines; children; insurance coverage; benefit utilization